2013
DOI: 10.3329/icpj.v2i4.14056
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Saponins rich fraction of Cassia auriculata Linn against various microbial strains

Abstract: In the present investigation, the saponins rich fraction of roots of Cassia auriculata L. was evaluated for antimicrobial activity against P. vesicularis, Streptococcus faecalis, Aeromonas hydrophilia, Salmonella typhae, Staphylococcus cohni, Serratia ficaria and E. coli at concentration of 12.5 mg/ml, 25 mg/ml, 37.5 mg/ml and 50 mg/ml. Antimicrobial activity of Cassia auriculata L. was carried out by well diffusion method. At maximum conc. i.e. 50mg/ml, antimicrobial effect of Saponin rich extract can be arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…They were concluded that L. vannamei immersed in water containing saponin could protect against V. alginolyticus infection [48]. [52]. It has been previously reported that C. albicans, and C. tropicalic were sensitive to the saponins of G. glabra and Q. saponaria [53].…”
Section: Defensive Rolementioning
confidence: 99%
“…They were concluded that L. vannamei immersed in water containing saponin could protect against V. alginolyticus infection [48]. [52]. It has been previously reported that C. albicans, and C. tropicalic were sensitive to the saponins of G. glabra and Q. saponaria [53].…”
Section: Defensive Rolementioning
confidence: 99%
“…There has been evidence of presence of saponins in traditional medicine preparations where administration is through oral means that is expected to lead to the hydrolysis of glycosides from terpenoids [37]. Studies carried out have shown medicinal plant extracts fractions rich in saponins are effective against microorganisms such as Escherichia coli, Salmonella typhi, Aeromonas hydrophilia and other fungal pathogens such as Candida albicans [38]. Saponins antimicrobial activity is attributed mainly to its capability of lysing microorganism's membranes rather than the surface tension of the extracellular medium [37].…”
Section: Discussionmentioning
confidence: 99%
“…The probable mechanism of antimutagenic activity of methanolic extract of Senna auriculata (L.) Roxb. bark, could be due to presence of excellent scavengers of reactive oxygen species (ROS) like singlet oxygen and/or superoxide anion radical whichplay a central role in multistage mutagenesis and carcinogenesis ( EFSA Scientific Committee, 2011 ; Deshpande et al, 2013a ; Deshpande et al, 2013b ).…”
Section: Pharmacological Actions Of Senna Auriculata (L) Roxbmentioning
confidence: 99%
“…The result indicates the saponins rich fraction of roots of Senna auriculata (L.) Roxb. might be exploited as natural drug for the treatment of several infectious diseases caused by these organisms ( Deshpande et al, 2013a ; Deshpande et al, 2013b ).…”
Section: Pharmacological Actions Of Senna Auriculata (L) Roxbmentioning
confidence: 99%
See 1 more Smart Citation